A COMPARATIVE RESEARCH OFTHE REGULARITIES OFTHE EXPLOSIVEPULSED DECOMPOSITION OFPETNCONTAINING GOLD AND SILVER NANOPARTICLES - S. G. Lukatova; O. V. Odintsova (Вестник Кемеровского государственного университета, 2015)
The paper presents a comparative research of the regularities of the explosive pulsed decomposition of nanocomposite PETN-gold and PETN-silver initiation by first and second harmonics of neodymium pulsed laser with duration at half-height 12 ns. The absorptivity and minimum energy density coefficients at which the explosive regime is realized were calculated for the wavelengths of the first and second harmonic of a neodymium laser in the nanoparticles radius range of 20 – 120 nm. Gold nanoparticles are perspective materials for use as a material of inclusions of optical detonator capsule based on the second harmonic of neodymium laser